(untitled) (Research, Society and Development, 2020)
Introduction: Hormone therapy reduces the vocal fundamental frequency of transgender men, but the evidence suggests that it does not modify other female communication characteristics, what may result in insufficient male communication patterns. Objective: To describe the voice therapy and its results on the voice of a 35-year-old transgender man. Methods: His main complaints were voice incompatible with his gender and vocal oscillation after hormonal treatment, started eight months prior to the study. Based on the speech evaluation, a therapeutic planning was elaborated aiming at developing: descending pitch at the end of sentences; decreasing vowel prolongation; "chest resonance"; decreasing pitch variation; costodiaphragmatic breathing; vocal projection and quality; maximum phonation time and pauses; decrease and stabilize fundamental frequency; adjust the resonance; decrease pitch and increase loudness; decrease the tension on the labial commissures; and develop male aspects of speech and language. Ten voice therapy sessions were held once a week, lasting 45 minutes each. Results: After voice therapy, there was decreased pitch variation during speech, increased pauses, focusing on the interlocutor, and “chest resonance”; this developed descending pitch at the end of sentences, decreasing vowel prolongation, and pitch variation, as an exercise to stimulate male voice markers and vocal stability. Even after the hormone-induced vocal changes, he still had complaints about his voice, which improved with the aid of voice therapy. Conclusion: Speech therapy provided the development of male vocal markers in his voice. It became compatible with his gender and allowed him to be recognized as a man by his voice, and to be pleased with it.